Chromosome fragility in patients with Fanconi anaemia: diagnostic implications and clinical impact. Issue 4 (7th January 2011) - Castella, Maria; Pujol, Roser; Callén, Elsa; Ramírez, Maria J; Casado, José A; Talavera, Maria; Ferro, Teresa; Muñoz, Arturo; Sevilla, Julián; Madero, Luis; Cela, Elena; Beléndez, Cristina; et al.
Abstract : Background: Fanconi anaemia (FA) is a rare syndrome characterized by bone marrow failure, malformations and cancer predisposition. Chromosome fragility induced by DNA interstrand crosslink (ICL)-inducing agents such as diepoxybutane (DEB) or mitomycin C (MMC) is the 'gold standard' test for the diagnosis of FA. Objective: To study the variability, the diagnostic implications and the clinical impact of chromosome fragility in FA. Methods: Data are presented from 198 DEB-induced chromosome fragility tests in patients with and without FA where information on genetic subtype, cell sensitivity to MMC and clinical data were available. Results: This large series allowed quantification of the variability and the level of overlap in ICL sensitivity among patients with FA and the normal population. A new chromosome fragility index is proposed that provides a cut-off diagnostic level to unambiguously distinguish patients with FA, including mosaics, from non-FA individuals. Spontaneous chromosome fragility and its correlation with DEB-induced fragility was also analysed, indicating that although both variables are correlated, 54% of patients with FA do not have spontaneous fragility. The data reveal a correlation between malformations and sensitivity to ICL-inducing agents. This correlation was also statistically significant when the analysis was restricted to patients from the FA-A complementation group. Finally, chromosome fragility does not correlate with the age of onset of haematological disease. Conclusions: This study proposes a new chromosome fragility index and suggests that genome instability during embryo development may be related to malformations in FA, while DEB-induced chromosome breaks in T cells have no prognostic value for the haematological disease.